1996
DOI: 10.1557/proc-422-199
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Study of Erbium and Oxygen Implanted Gallium Nitride

Abstract: A systematic study of photoluminescence (PL) of Er and O ion implanted and annealed n-type GaN grown on R-plane sapphire (A12O3) was performed. The Er implants ranged from 2 × 1013 to 1 × 1015 Er++/cm2, and the O co-implants ranged from 1014 to 1016 O+/cm2. The resulting nine different combinations of GaN:Er,O were annealed at 600 °C (4 hrs. in N2), 700 °C (1.5 hrs. in N2), 800 °C (0.75 hr. in NH3), and 900 °C (0.5 hr. in NH3) Following each annealing step, the Er3 -related PL at 1.54 μm was measured from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…18 For the implanted sample the peak intensity decreased by a factor of 4 and the integrated intensity decreased by a factor of 1.8 over the temperature range 11-295 K, consistent with previous reports. 4,8,9,11,12 The peak emission lifetime at 295 K was determined to be 2.3Ϯ0.1 ms which is similar to the value reported by Torvik et al 9 The band edge spectra of the two samples are provided in Fig. 2 for temperatures of 11 and 295 K. Both band edge spectra show a significant amount of structure around 390 nm at 11 K. These spectra indicate that both samples have states within the semiconductor band gap.…”
Section: ͓S0003-6951͑98͒02010-5͔supporting
confidence: 82%
See 1 more Smart Citation
“…18 For the implanted sample the peak intensity decreased by a factor of 4 and the integrated intensity decreased by a factor of 1.8 over the temperature range 11-295 K, consistent with previous reports. 4,8,9,11,12 The peak emission lifetime at 295 K was determined to be 2.3Ϯ0.1 ms which is similar to the value reported by Torvik et al 9 The band edge spectra of the two samples are provided in Fig. 2 for temperatures of 11 and 295 K. Both band edge spectra show a significant amount of structure around 390 nm at 11 K. These spectra indicate that both samples have states within the semiconductor band gap.…”
Section: ͓S0003-6951͑98͒02010-5͔supporting
confidence: 82%
“…[4][5][6][7][8][9][10][11][12] GaN is a wide band-gap III-V semiconductor useful as a short wavelength emitter and detector. 13 Previous investigations of Er luminescence in GaN:Er have been promising with most researchers finding only an ϳ50% decrease in photoluminescence intensity over the temperature range 6-300 K. 4,8,9,11 This is a significant improvement over the two-to-three order of magnitude decrease of Er luminescence intensity in GaAs:Er. 2 The studies performed on GaN:Er so far have principally focused on Er implanted into GaN.…”
Section: ͓S0003-6951͑98͒02010-5͔mentioning
confidence: 99%
“…10 We have previously shown that single anneals of implanted GaN:Er,O at 800°C ͑45 min͒ or 900°C ͑30 min͒ are comparable. 17 It was also shown in the same article that single anneals are preferable to multiple anneals ͑600-900°C͒ or ''low-temperature'' anneals ͑600-700°C͒ when attempting to maximize the Er 3ϩ -related PL intensity at 1539 nm. In this study the integrated PL from samples that have been annealed at 800°C ͑45 min͒ and 900°C ͑30 min͒, are compared to samples annealed at 800°C ͑45 min͒ or 900°C ͑30 min͒.…”
Section: Annealingmentioning
confidence: 95%
“…This corresponds to an indirect excitation of the Er 3+ ions by electron-hole pairs. A few experiments have been carried out in which the Er 3+ ions have been excited directly by the optical pump radiation [14]. In this case, the Er 3+ ions are excited directly by the optical pump, with the energy of the laser radiation equal to that of one of the higher energy states of the Er 3+ ion.…”
Section: Optical Excitation Spectroscopymentioning
confidence: 99%